The Effect of Attitudes, Subjective Norms, and Perceived Behavioral Control on MSMEs’ Intention to Obtain Halal Certification in Pamekasan - Safira Adibatul Faruq (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
This study aims to analyze the effect of attitude, subjective norms, and perceived behavioral control on the intention of Micro, Small, and Medium Enterprises (MSMEs) to apply for halal certification in Pamekasan Regency based on the Theory of Planned Behavior. This research employs a quantitative approach with an explanatory design. Data were collected through questionnaires distributed to culinary MSME actors using a purposive sampling technique. The variables examined include attitude, subjective norms, perceived behavioral control, and intention to obtain halal certification. The findings indicate that MSME actors generally have a positive attitude toward halal certification, particularly in enhancing consumer trust and business competitiveness. However, subjective norms are not yet strong enough to significantly influence intention, while perceived behavioral control is identified as the most dominant inhibiting factor due to limited knowledge of procedures, perceived high costs, and procedural complexity. Overall, MSME intention remains suboptimal, requiring improved socialization, assistance, and simplified certification procedures.